Mitochondrial DNA ancestry, HPV infection and the risk of cervical cancer in a multiethnic population of northeastern Argentina - Badano, Inés (2018)
Fil: Badano, Inés. Universidad Nacional de Misiones. Facultad de Ciencias Exactas, Químicas y Naturales. Laboratorio de Biología Molecular Aplicada; Argentina.